Net section resistance of bolted S690 steel angles subjected to tension. (June 2020) - Yam, Michael CH; Ke, Ke; Jiang, Binhui; Lam, Angus CC
Abstract: Net section rupture is a common failure mode of bolted tension members. In particular, the net section capacity of tension angle is significantly affected by the effect of shear lag. This paper reports the tensile test results of twelve high strength steel angles and six normal steel angles of grade S690 and S275, respectively. The test parameters included steel grades, connection length (bolt number) and out-of-plane eccentricity. All the specimens were failed by net section rupture. Finite element (FE) analysis was used to simulate the structural behaviour of the test specimens and to further interpret the test results. The test and the numerical analysis results showed that the test efficiency of tension angles, which was defined by the ratio of the ultimate test load to the calculated net section resistance, was sensitive to the material ductility and the connection details (i.e. out-of-plane eccentricity and connection lengths). The effectiveness of the available design specifications for quantifying the net section resistance of S690 steel angles was evaluated. A design approach proposed by Yam and colleagues considering the influence of material mechanical characteristics and connection configurations was also revisited. It was found that the current design specifications produced inconsistent predictions of net section resistance of tension angles, whereas the method proposed by Yam and colleagues gave good predictions of net section resistance of bolted S690 steel angles. Highlights: Structural performance of bolted S690 and S275 steel angle is examined. The influence of steel grades and connection configuration is studied. Test observations are strengthened by finite element model results. Design comments are proposed.